(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to identify the external feedback for students of the College of Physical Education and Sports Sciences - University of Al-Muthanna. In addition to identifying the offensive skills in basketball and the effect of feedback on the stability and compound shooting skills of the students of the College of Physical Education and Sports Sciences - Al-Muthanna University. (68) student. The homogeneity of the research sample was conducted, and the main experiment was conducted during the period (25/3/2021 to 22/4/2021) and the data were processed statistically